Science teachers can teach computational thinking through distributed expertise - Tucker-Raymond, Eli; Cassidy, Michael; Puttick, Gillian (Computers and education, 2021)
Content area K-12 teachers are increasingly asked to integrate computing and computational thinking into their classrooms, yet they often have little experience with computing. The purpose of this study was to understand how science teachers, new to computing and integrating computational thinking into their classrooms, supported students as computational problem solvers. In the project from which this research was drawn, 8th grade science teachers in three US school districts integrated computer game design into their study of climate systems and climate change. We conducted participant observation, collected teacher implementation logs and interviewed 15 teachers engaged in the three-year design research project, Building Systems from Scratch. Analysis through grounded theory yielded several results related to teachers’ orientations, strategies, and use of resources to create systems of distributed expertise. We identified five major themes: a) releasing responsibility to students, b) co-learning with students, c) encouraging students’ independent problem solving, d) building interdependence among students, and e) providing multiple other resources. Findings are discussed in relation to the literature on integrating computational thinking into content area classrooms. •Science teachers' orientations to incorporating computational thinking practices.•Science teachers distribute expertise to support computational problem-solving.•Opportunities and tensions for independent student computational problem-solving.•Strategies for teachers new to integrating computational practices.